Greek students' attitudes, perception and knowledge regarding generic medicines in times of economic crisis: a cross-sectional study - Domeyer, Philippe J.; Katsari, Vasiliki; Sarafis, Pavlos; Aletras, Vassilis; Niakas, Dimitris (My University, 2018)
Background: The penetration of generic medicines in the pharmaceutical market is influenced, among others, by the consumer's attitude upon them. The attitude of students in health management and recent alumni is particularly important, as they constitute tomorrow's policymakers. The aim of our study was to assess their attitude, perception and knowledge towards generic medicines. Methods: A cross-sectional study was undertaken, involving students in Health Management and recent alumni. The ATtitude TOwards GENerics (ATTOGEN) validated questionnaire was used, which consists of 18 items, yielding 6 scales (trust, state audit, knowledge, drug quality, drug substitution and fiscal impact), with all item responses expressed on a 5-point Likert scale and higher scores denoting greater disagreement. Correlation coefficients were computed and independent sample tests were performed using non-parametrical statistical methods. Results: A total of 1402 students were interviewed, with a female predominance (62.88%). The mean (SD) scores for the six scales of the ATTOGEN questionnaire were: Trust: 2.877 (0.940), State audit: 3.251 (0.967), Knowledge: 1.537 (0.688), Drug quality: 2.708 (0.971), Drug substitution: 3.828 (1.127) and Fiscal impact: 2.299 (0.860). Trust over generics was statistically significantly associated with all ATTOGEN scales (all p < 0.001). In addition, the increased level of knowledge about generics was associated with recognition of the generic medicines' quality equivalence (p < 0.001) and positive fiscal impact (p = 0.018). Pharmacists declared having a superior knowledge of generic medicines, being more satisfied with the information they receive about them and strongly believing in drug substitution (p < 0.001). Comparatively to other professionals, pharmacists also indicated substantial differences between branded and generic medicines more often (p < 0.001). They also argued to a greater extent that generic medicines were invented and promoted to resolve the financial crisis of social security institutions at the expense of citizens (p < 0.001). Conclusions: This study demonstrated a mixed attitude of students regarding generic medicines. Trust and knowledge emerged as key factors shaping the students' attitude towards generics. Among students, pharmacists exhibited a distinct response pattern. This study underlines the importance of addressing and correcting health management students' misbeliefs about generics' quality and utility.
Keywords: Attitude; Drug substitution; Fiscal impact; Generics; Greece; Knowledge; Quality of generics; State audit; Students; Trust in generics